Case Report: Glaucoma in an Infant With Retinopathy of Prematurity - Lenis, Tamara Lee; Ledesma Vicioso, Nahomy; Reddy, Varun; Kovacs, Kyle D; Van Tassel, Sarah H; Orlin, Anton (Frontiers in Pediatrics, 2021)
Retinopathy of prematurity (ROP) is a leading cause of childhood blindness that occurs due to incomplete development of retinal blood vessels in preterm infants. Glaucoma is an ocular co-morbidity in some patients with ROP, and it may be associated with immature anterior chamber development, ROP itself, or the treatment for ROP. There have been a few reports of narrow angle glaucoma after laser treatment for ROP. In this case report we describe the course of a female infant born at 24 weeks and 5 days gestational age with treatment-requiring ROP treated with laser photocoagulation who subsequently developed very elevated intraocular pressure and shallow anterior chambers without pupillary block. The patient required bilateral ab externo trabeculotomy for elevated intraocular pressure, which normalized after the procedure. Differing from previous glaucoma presentations in this setting, we illustrate a case of elevated intraocular pressure and anterior chamber narrowing after laser therapy without pupillary block or synechiae. The possible multifactorial etiology of glaucoma in this patient, including incomplete angle development, ischemia, and laser treatment, highlight the need for glaucoma screening in patients with ROP, both in the short and long term.